Learning Dance to Improve Motor Skills of Lightweight Palsy Cerebral Patients at YPAC Semarang - Rimasari Pramesti Putri; Bintang Hanggoro Putro (Publikasi Indonesia, 2021)
The National Education System Law Number 20 of 2003 states,